OPTIMISME vs PESIMISME: STUDI DESKRIPTIF TENTANG PROFIL OPTIMISIME MAHASISWA - Prayogi, Fiki (LPPM STKIP PGRI Bandar Lampung, 2020)
This study aims to determine the optimism profile of students studied by exploring the tendencies of optimism and pessimism that exist in each student. The approach used in this research is quantitative descriptive survey type. Determination of the sample is done by random sampling of 154 students guidance and counseling. The research instrument uses an optimism scale which is an adaptation of the Life Orientaion Test (LOT) instrument. The data analysis technique uses descriptive quantitative data analysis. The results showed 63.64% of students had a high level of optimism, 35.06% in the medium category, and 1.30% in the low category. This finding shows that the majority of students have a high level of optimism. In addition, from various levels of optimism, it is also known that 92.21% of students have a tendency to be optimistic compared to pessimists, 4.54% tend to be pessimistic rather than optimistic, and 3.25% have a balanced tendency between optimism and pessimism for each individual. More in-depth discussion and research must be conducted to find out whether a high level of optimism has a positive impact or a negative impact on students, given the high optimism also needs to be balanced with a healthy level of realism.